A new biorefinery platform for producing (C2-5) bioalcohols through the biological/chemical hybridization process. (September 2020) - Jung, Sungyup; Kim, Hana; Tsang, Yiu Fai; Lin, Kun-Yi Andrew; Park, Young-Kwon; Kwon, Eilhann E.
Highlights: Current status and challenges of bioalcohol production process were discussed. A hybrid platform for bioalcohol production using waste materials was addressed. Advantages for use of anaerobic digestion intermediates were discussed. Techno-economic analysis for new and present processes was compared. Abstract: This review presents an emerging biorefinery platform for C2-5 bioalcohol production through chemical synthesis using the organic waste materials. Bioalcohols are the most commercialized carbon–neutral transportation fuels, compatible with existing an internal combustion (IC) engine. However, current bioalcohol fermentation processes have made from sugar-rich edible crops. Also, carbon loss from the fermentation process is substantial. To minimize carbon loss, volatile fatty acids (VFAs) can be utilized as a raw material for bioalcohol production. Thus, a two-step chemical upgrading of VFAs into C2-5 alcohols is summarized in comparison with current challenges of biological fermentation processes for bioalcohol production. This review also provides the prospect of the hybrid biological/chemical process, presenting the technical advantages of the system. Finally, economic viability of hybridized process for bioalcohol production is compared with the current biological process.